2020
DOI: 10.13169/islastudj.5.2.0152
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of Hate Industry: Islamophobia in the Western Public Sphere

Abstract: Minority communities across the globe are increasingly being targeted for vilification and demonization which consequently result in their marginalization and persecution, among other forms of physical, psychological, structural and cultural violence. These may be on account of race, religion, ethnicity, sexual orientation, disabilities or other demographic indicators—a phenomenon which summatively came to be known as hate speech/crime. When such violence ballooned beyond bearable level against the black commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 31 publications
(43 reference statements)
0
14
0
1
Order By: Relevance
“…However, Islamophobia is certainly a social evil that has taken deep root in the world, especially after the attacks of September 11, 2001. In countries where the Muslim community has a substantial share in demography, conservative political parties have been regularly using Islamophobia as a political agenda to garner votes (Bukar, 2020). The COVID-19 pandemic provided another opportunity to conservative and right-wing political leaders and their supporters to target Muslims.…”
Section: Discussionmentioning
confidence: 99%
“…However, Islamophobia is certainly a social evil that has taken deep root in the world, especially after the attacks of September 11, 2001. In countries where the Muslim community has a substantial share in demography, conservative political parties have been regularly using Islamophobia as a political agenda to garner votes (Bukar, 2020). The COVID-19 pandemic provided another opportunity to conservative and right-wing political leaders and their supporters to target Muslims.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-Muslim sentiments and hatred towards Muslims have increased in the west over the past few decades. 2 In light of the proof on Islamophobia, an inductive approach is used to understand the root causes. A number of philosophical concepts is existent align with the ideology of this research.…”
Section: Methodsmentioning
confidence: 99%
“…1 Furthermore, current surveys have found that citizens in the western world have a robust negative perspective and feelings about Muslim communities and Islam. 2 The main goal of this study is to explain Islamophobia and why there is violence and hatred against Muslim communities in the west. Several studies have portrayed the image of Islam and Muslim people from the perspective of western people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selain itu, juga berkaitan dengan bentuk diskriminasi lainnya seperti penolakan pekerjan serta urusan politik dan kebijakan negara. Pendapat Donald Trump merupakan contoh komentar yang berangkat dari popularitas sentimen yang berkaitan dengan Islamofobia (Bukar, 2020).…”
Section: Hasil Temuan and Diskusiunclassified